Treatment of Rheumatoid Arthritis With Anti–Tumor Necrosis Factor or Tocilizumab Therapy as First Biologic Agent in a Global Comparative Observational Study. Issue 10 (6th September 2017) - Choy, Ernest H.; Bernasconi, Corrado; Aassi, Maher; Molina, Jose Fernando; Epis, Oscar Massimiliano
Abstract : Objective: To compare clinical effectiveness between tocilizumab and tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA) and inadequate response to conventional synthetic disease‐modifying antirheumatic drugs initiating biologic therapy. Methods: Patients prescribed tocilizumab (intravenous) or TNFi were prospectively observed in routine clinical practice for 52 weeks across 158 sites in 26 countries. The primary observation was the change from baseline in Disease Activity Score based on 28 joints using the erythrocyte sedimentation rate (DAS28‐ESR) at week 24 using analysis of covariance for between‐groups comparison. Secondary end points included Clinical Disease Activity Index (CDAI) and patient‐reported outcomes at weeks 24 and 52. Results: Of 1, 216 patients, 35% initiated tocilizumab and 65% initiated TNFi. RA duration was shorter, and disease activity and corticosteroid use were higher in tocilizumab patients. Tocilizumab‐treated patients had greater improvement in DAS28‐ESR at weeks 24 and 52 (week 24 difference [95% confidence interval] in adjusted means: −0.831 [−1.086, −0.576]; P < 0.001). Change from baseline in CDAI was also greater with tocilizumab (adjusted means difference: week 24, −3.48; week 52, −4.60; both P < 0.001). Tocilizumab‐treated patients had more improvement in the Health Assessment Questionnaire disability index than TNFi‐treated patients ( P < 0.05). The cumulative probability of drug discontinuation at week 52 was lower with tocilizumab (15%) than TNFi (27%; P < 0.001, unadjusted analysis). Unadjusted frequencies (events per 100 patient‐years) for tocilizumab and TNFi were 6.44 and 11.99 for serious adverse events, 1.98 and 5.03 for serious infections, and 0.74 and 0.77 for deaths, respectively. Conclusion: Patients initiating tocilizumab experienced greater effectiveness and drug survival than those initiating TNFi in an observational setting.